PENGARUH APLIKASI RHOZOBIUM DAN PUPUK NPK, BOKASHI TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KEDELAI (GLYCINE MAX L Merrill) PADA TANAH GAMBUT - Marhani Marhani (Agroland: Jurnal Ilmu-ilmu Pertanian, 2019)
The domestic need of soybeans in Indonesia has yet to be met due to its low productivity. One effort to improve it is through the provision of rhizobium, NPK fertilizer and bokashi. The purpose of this study was to determine the interaction effects of rhizobium, NPK fertilizers and bokashi in peat soil on growth and yield parameters of soybean. The research used a two-factorial Randomized Block design (RBD) with three replicates.  The first factor was rhizobium (without and with rhizobium).  The rhizobium added was at a rate of 20 g legin/kg seed. The second factor is the rates of fertilizers (with no fertilizer added, 25 kg NPK/ha, 50 kg NPK/ha, 75 kg NPK/ha and 2 ton bokashi/ha).  The results showed that the interaction of the rhizobium and the NPK fertilizer added at 20 kg/ha was significantly affected plant height, number of pods per plant, number of filled pods per plant, number of seeds per plant but it was not significant on leaf number, number of seeds per pod, weight of 100 seeds and number of root nodules. The interaction of the rhizobium and the NPK fertilizer added at 50 kg/ha significantly affected plant height, number of pods per plant, number of seeds per pod, number of seeds per plant, number of root nodules but no significant effect on leaf number and weights of 100 seeds. The interaction of the rhizobium and the NPK fertilizer added at 75 kg/ha significantly affected plant height, number of pods per plant, number of pods per plant, number of seed pods per plant but no significant effect on leaf number, number of seeds per pod, weight of 100 seeds and number of root nodules. The interaction of the rhizobium and the bokashi significantly affected number of pods per plant, number of filled pods per plant, number of seeds per plant but no significant effect on plant height, number of leaves, weight of 100 seeds and number of nodules.